Analysis of St. 42 Steel Hardness After Being Heated to 8000c And Quickly Cooled With Fresh Water by Applying Rockwell Method - Ketut Rimpung (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2018)
The hardness of machine components which, in operation time, collide and rub against each other and are made of St.42 steel needs to be found out. Therefore, research on the hardness of St.42 steel especially those which are heated needs to be carried out so that it can be chosen as machine component properly. This research tests the change of the surface hardness by applying Rockwell method and is the continuation from a former research. Steel is a technical material which is often used as machine components, so that its strength against external loads is really needed to be known. External loads which are often occurred on machine components are friction load, torsion load, tensile load, bent load and mash load. This research aims to find out how much the change of the hardness of standard St.42 steel surface after being heated at temperature of 8000C and quickly cooled by using fresh water which is carried out in laboratory of material testing, Department of Mechanical Engineering, State Polytechnic of Bali. The result shows that the hardness of the surface of steel which is heated until 8000C and quickly cooled by using fresh water is more lenient than the standard St.42 steel, although it is tested by applying either Rockwell B (HRB) or Rockwell C (HRC) methods. The change of the strength based on Rockwell B method shows the decrease in surface hardness until 19,81%; from 29,93 (Kgf/mm2) to 24,0 (Kgf/mm2). In Rockwell C method there is also decrease in surface hardness which is equal to 20,23%; from 54,7(Kgf/mm2) to 43,63 (Kgf/mm2).